ECOENDOSCOPIA EN LA PATOLOGÍA BILIAR Y PANCREÁTICA Endosonography in Pancreatobiliary Disorders - Osvaldo Díaz-Canel Fernández; Rolando Martínez López; Julián Ruiz Torres; Vivianne Anido Escobar; Liliana Pernía González (Universidad de Ciencias Médicas de La Habana, 2007)
La ecoendoscopía o ultrasonografía endoscópica (USE) permite una buena visualización de la vesícula, vía biliar, del parénquima pancreático y de las estructuras vasculares vecinas a estos órganos. 1,2 Tiene una alta resolución debido a la cercanía del transductor y a las elevadas frecuencias. Junto con otras técnicas de imagen que se están desarrollando, como la tomografía computarizada (TC) helicoidal y la colangiopancreatografía por resonancia magnética (CPRM) son técnicas seguras y que ofrecen resultados prometedores en el estudio de los tumores, permitiendo la estadificación locoregional de éstos, llegar al diagnóstico de cálculos pequeños de la vía biliar principal que no son visualizados por US abdominal y lograr una visualización más fiel de la glándula pancreática y de las estructuras vasculares vecinas. 3,4, 5 Endoscopic ultrasound is a minimally invasive imaging modality that provides high - resolution images of the extrahepatic biliary tree and the surrounding structures. It has been shown to be accurate for the detection and staging of bile duct and gallbladder cancer, and is especially useful for small tumors. Intraductal techniques, which are still in evolution, may provide even more information about the etiology and extent of biliary structures and mural tumors. EUS has also been shown to be useful for the detection of biliary stones and sludge when transabdominal ultrasound is not diagnostic. In many cases, diagnostic EUS is needed. 1, 2, 3 Endosonography produces detailed images of the pancreas and surrounding blood vessels and provides both accurate detection and staging of malignant lesions and the means for making a tissue diagnosis.The instruments and techniques for endosonography continue improving, and at present EUS can be considered a promising minimally invasive tool for evaluating the pancreatobiliary disorders. 4, 5